Analytic solution of a circular plate whose boundary is elastic fixed on elastic foundation (International Journal of Architecture and Urbanism, 2023)
OnÂ this paper an analysis of a circular plate whose boundary is elastic fixed on an elastic foundation is presented. First, we set up a schema, establish a mathematic model on it. The model becomes a boundary value problem of partial differential equation. Â By solving the problem, deflections and internal forces in the circular plate are calculated concretely.